Identification of sintering and slagging materials: characterization of coal, ash and non-coal rock fragments - Maphala, Tshifhiwa (My University, 2009)
During a coal-conversion process, some components of the mineral matter in the coal such as organic minerals, organically-bound and inorganic elements and extraneous rock fragments may interact with each other to generate submicron ash particles, volatile compounds and ash clinkers, and can give rise to fouling, slagging, abrasion, stickiness and corrosion within coal conversion units. It is proposed that some fluxing minerals such as pyrite, calcite, and ankerite and to a lesser extent dolomite or inorganic elements present in the extraneous rock fragments such as sandstone, siltstone, mudstone and carbonaceous shale could react with free aluminium silicates (clays) at elevated temperatures to form a melt, and contribute to the slagging problems during coal-conversion. In order to manage this, and hence to minimise its effects, it is important to better understand the chemical and mineralogical properties of the individual rock fragments included in the feedstock coal. In this study, a detailed characterization of rock fragments was undertaken in order to better understand their chemical and mineralogical properties. A mineralogical characterization on the feed coal and corresponding ash clinker was conducted in order to understand the mineral composition, and compared to the determined mineralogy of rock fragments mineralogy. Crystalline phases (minerals) qualification and quantification were determined using powder X-ray diffraction (PXRD). Different Rietveld based methods were used for quantification of minerals and compared to each other. Quantitative evaluation of minerals by scanning electron microscope (QEMSCAN) and normative methods were used as a comparative tool and confirmation of minerals discrimination. The major minerals determined were quartz, kaolinite and muscovite/illite with minor occurrences of feldspar in the form of microcline.